Facework and Prosocial Teasing in a Synchronous Video Communication Exchange - Pennock-Speck, Barry; Clavel-Arroitia, Begoña (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2019)
This study centres on the analysis of prosocial teasing during a videoconference (telecollaboration) exchange between mixed-gender adolescent secondary school students from Spain and Germany. We contend that the provocative elements present in prosocial teasing activate a play frame, in Gregory Bateson’s terms, in which seemingly hostile face acts can be interpreted as playful behaviour. We argue that successful teasing can ultimately enhance the face of the teaser and that of the person being teased and thus build up rapport between them. Our analysis of the facework in the interaction during this telecollaboration exchange is based on Erwin Goffman’s notions of face, demeanour and deference and stands in opposition to the dominant (im)politeness paradigm put forward by Jonathan Culpeper, which has its roots in Penelope Brown and Stephen C. Levinson’s seminal work. Keywords: facework; teasing; telecollaboration; language learning